Surgical Outcomes In The Frequency, Etiology, Direction, Severity (feds) Classification System For Shoulder Instability. Issue 3 (27th March 2020) - Magnuson, Justin A.; Wolf, Brian R.; Cronin, Kevin J.; Jacobs, Cale A.; Ortiz, Shannon; Kuhn, John E.; Group, MOON Shoulder; Hettrich, Carolyn M.
Objectives: The Frequency, Etiology, Direction, Severity (FEDS) system is a reliable and reproducible classification of glenohumeral instability. Frequency is defined as Solitary (1), Occasional (2-5), or Frequent (>5) episodes per year; etiology as Traumatic or Atraumatic; direction as Anterior, Posterior, or Inferior; and severity as a Subluxation or Dislocation. 36 total combinations are possible, named by the first letter of each variable in order. The purpose of this descriptive study was to investigate epidemiology, surgical outcomes, and failure using FEDS in patients undergoing surgery in a large multicenter cohort of prospectively enrolled patients. Methods: 1204 patients undergoing surgery were assigned to FEDS categories. Two-year follow-up at time of analysis was available for 629 patients (85.7% of those eligible based on date of surgery). Those categories consisting of at least 5% of patients were further analyzed by patient reported outcomes (PROs) and failure rates for a total of 466 patients. PROs included American Shoulder and Elbow Surgeons score (ASES), Western Ontario Shoulder Instability index (WOSI), and Single Assessment Numeric Evaluation (SANE). Failure benchmarks included rates of recurrent subluxation, dislocation, and revision surgery. Results: Sixteen categories represented at least one percent of patients. Occasional Traumatic Anterior Dislocation (OTAD) was the most common category with 16.4% of patients. Five other anterior categories (STAS, OTAS, FTAS, STAD, FTAD) and one posterior category (STPS) represented at least 5%. PROs and failure rates for anterior categories are summarized in Figure 1. PROs improved significantly for each category. A downward trend in WOSI and ASES was noted in particular with increasing frequency of the dislocation groups. The highest rates of each type of failure occurred in the occasional and frequent groups for both dislocation and subluxation. Low rates of failure occurred in STPS, with 17.9% reporting subluxation, 3.6% dislocation, and no revisions. Conclusion: While overall success was good, different FEDS categories showed varying degrees of improvement and failure rates, indicating that the system can be used to provide prognostic insight for presurgical education. Overall, outcomes for traumatic anterior instability decreased with higher initial frequency, showing worse PROs and higher failure. Frequency appeared to have the greatest effect on outcomes. Early surgical intervention may be beneficial in preventing progression to more severe FEDS categories, with higher frequency having previously been associated with both higher rates of bone loss and greater time between initial event and surgical stabilization. :